Development of Tadris Al-'Arabiyyah Al-Mukatssaf (TAM) Textbook, Based on Contextual Teaching and Learning (CTL) - Afyuddin, Moh Sholeh; Muslimah, Maziyyatul; Kholis, Muhammad Nur; Rahmawati, Rina Dian (UIN Syekh Wasil Kediri, Indonesia, 2023)
Tadris al-'Arabiyyah al-Mukatssaf (TAM) is a course given to semester 1 students of Arabic Language Education, Institut Agama Islam Negeri (IAIN) Kediri. This course aims to prepare new students with standard Arabic language skills so they will be able to learn Arabic language courses in the next semester easily. The development of this textbook is based on contextual teaching and learning (CTL) because CTL is a student-oriented approach which can lead students to become more active and can generate self-directed in learning. The textbook development uses the ADDIE procedure with 5 development steps and ends with an experimental test to reveal the effectiveness. This research produced a textbook Tadris al-'Arabiyyah al-Mukatssaf based on Contextual Teaching and Learning with its seven principles, which are: constructivism, inquiry, questioning, learning community, modeling, reflection and authentic assessment. This textbook contains 21 dars (units). Each dars (unit) contains 4 material: 1) ta'bir al-shuurah, 2) hiwar, 3) nash qiraah, and 4) qawaid. In hiwar, nash qiraah and qawaid are equipped with practice questions and a list of mufrodat and Arabic expressions. The results of the effectiveness test with the pre-test and post-test designs revealed that the average post-test score was at 65.33, higher than the pre-test average score at 56.35. Total T count of 9.90 is higher than T table of 1.98 which means that Ha is accepted and Ho is rejected. With a Pearson correlation value of 0.64 greater than 0.05, the use of books proved to be effective.